2018
DOI: 10.1097/aog.0000000000002390
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Low-Risk Endometrial Cancer and Complex Atypical Hyperplasia With the Levonorgestrel-Releasing Intrauterine Device

Abstract: Levonorgestrel-releasing IUD therapy for the conservative treatment of complex atypical hyperplasia or early-grade endometrial cancer resulted in return to normal histology in a majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
129
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 22 publications
5
129
0
Order By: Relevance
“…Some patients cannot be operated on due to advanced age, morbid obesity, and/or medical comorbidities [2,17]. In addition, some young patients wish to preserve their fertility [2,28].…”
Section: Roc Curvementioning
confidence: 99%
See 1 more Smart Citation
“…Some patients cannot be operated on due to advanced age, morbid obesity, and/or medical comorbidities [2,17]. In addition, some young patients wish to preserve their fertility [2,28].…”
Section: Roc Curvementioning
confidence: 99%
“…In such situations, intraoperative frozen sectioning may play an important role. In addition, older patients and those with medical comorbidities, and younger patients who want to preserve their fertility, are not eligible for the operation [17]. Thus, preoperative evaluation is more important in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment modalities for EAH or early-stage endometrioid endometrial cancer (EEC) patients are mainly progestin therapies, including medroxyprogesterone acetate (MPA), megestrol acetate (MA), and levonorgestrel intrauterine system (LNG-IUS) [4][5][6]. Reports showed 75-85% of EAH and 50-75% of EEC patients could achieve complete response (CR) [7,8]. Dilatation and curettage (D&C) is a traditional diagnostic method in this fertility-sparing setting [9].…”
Section: Introductionmentioning
confidence: 99%
“…Pal et al reviewed 46 patients treated with LNG-IUD and found similar response rates of 75-80% among women treated for EAC and EHA. [41] Interestingly women with larger uterus size, and those with lack of exogenous progesterone effect in the pathology were found to have a lower likelihood to respond. Previous studies reported that the average time to response was six months.…”
Section: Recent Results and Pregnancy Outcomesmentioning
confidence: 98%